Decolorization of Direct Black 22 by Photo Fenton like Method Using UV Light and Zeolite Modified Zinc Ferrite: Kinetics and Thermodynamics - Serap Findik (Acta Chimica Slovenica, 2022)
In this study, a heterogeneous catalyst was prepared to enhance photo-Fenton like oxidation of Direct Black-22 (DB-22). Zeolite modified with zinc ferrite was used as a catalyst. The prepared catalyst was characterized using FTIR, SEM, EDS and XRD. The effect of various parameters like catalyst modification with HCl, H2O2 amount, catalyst amount, CaCl2 amount, initial pH, initial concentration and temperature on the decolorization of DB-22 was studied under UV light. Kinetic and thermodynamic properties were investigated. The highest decolorization of DB-22 was found to be 93.3% under the following conditions: initial concentration: 0.070 g/L, initial temperature: 25 °C, original pH, H2O2 amount: 2.78 g/L, m-ZZF amount: 3 g/L, CaCl2 amount: 3.75 g/L, reaction time: 60 min and UV light. The activation energy was found to be -14.76 kJ/mol under the studied conditions. The decolorization reaction was an exothermic reaction, and the calculated reaction enthalpy was -17.31 kJ/mol. The activation entropy was calculated to be -0.326 kJ/mol. The standard Gibbs free energy change of the activation had a positive value, and it increased with increasing temperature.